MODERN TYPES OF IMMUNOENZYME ANALYSIS METHODS OLD PROBLEMS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The basis of any ELISA variant is the determination of enzymatic reaction products in the examination of tested samples in comparison with negative and positive controls. The method has high sensitivity and specificity, which is 90%.